Rare Presentation of Postsurgical Pyoderma Gangrenosum Presenting as Necrotizing Soft Tissue Infection - Flynn, Rod L. (Adv Skin Wound Care, 2019)
Pyoderma gangrenosum (PG) is a rare inflammatory neutrophilic dermatosis believed to be mediated by an autoimmune reaction. Typical treatment includes autolytic debridement, management of exudate, protection from trauma, and steroid therapy. A diagnosis of exclusion, PG is frequently mistaken for a wound infection, but antibiotics do not alleviate the condition. Incision and debridement has been observed to cause further spread of the lesions because of pathergy resulting from the additional trauma. This case report describes a patient who was misdiagnosed with necrotic soft tissue infection that was actually postsurgical PG.